Covalent IR820-PEG-diamine nanoconjugates for theranostic applications in cancer - Fernandez-Fernandez A (Dove Medical Press, 2014)
Alicia Fernandez-Fernandez,1,2 Romila Manchanda,1,3 Denny Carvajal,1,4 Tingjun Lei,1,5 Supriya Srinivasan,1 Anthony J McGoron11Biomedical Engineering Department, Florida International University, Miami, FL, USA; 2Physical Therapy Department, Nova Southeastern University, Fort Lauderdale, FL, USA; 3Chemistry Department, Galgotias University, Greater Noida, UP, India; 4Mount Sinai Medical Center, 5Cirle, Miami, FL, USAAbstract: Near-infrared dyes can be used as theranostic agents in cancer management, based on their optical imaging and localized hyperthermia capabilities. However, their clinical translatability is limited by issues such as photobleaching, short circulation times, and nonspecific biodistribution. Nanoconjugate formulations of cyanine dyes, such as IR820, may be able to overcome some of these limitations. We covalently conjugated IR820 with 6 kDa polyethylene glycol (PEG)-diamine to create a nanoconjugate (IRPDcov) with potential for in vivo applications. The conjugation process resulted in nearly spherical, uniformly distributed nanoparticles of approximately 150 nm diameter and zeta potential -0.4±0.3 mV. The IRPDcov formulation retained the ability to fluoresce and to cause hyperthermia-mediated cell-growth inhibition, with enhanced internalization and significantly enhanced cytotoxic hyperthermia effects in cancer cells compared with free dye. Additionally, IRPDcov demonstrated a significantly longer (P<0.05) plasma half-life, elimination half-life, and area under the curve (AUC) value compared with IR820, indicating larger overall exposure to the theranostic agent in mice. The IRPDcov conjugate had different organ localization than did free IR820, with potential reduced accumulation in the kidneys and significantly lower (P<0.05) accumulation in the lungs. Some potential advantages of IR820-PEG-diamine nanoconjugates may include passive targeting of tumor tissue through the enhanced permeability and retention effect, prolonged circulation times resulting in increased windows for combined diagnosis and therapy, and further opportunities for functionalization, targeting, and customization. The conjugation of PEG-diamine with a near-infrared dye provides a multifunctional delivery vector whose localization can be monitored with noninvasive techniques and that may also serve for guided hyperthermia cancer treatments.Keywords: fluorescent imaging, hyperthermia, image-guided therapy, nanotechnology